Methods and procedures for a systemic functional linguistic analysis: An investigation into clause complexing relations - Sridevi Sriniwass (Journal of Modern Languages)
This paper outlines a methodology which is consistent with a heuristic-grounded theory- document analysis- qualitative approach (Patton, 1990, Creswell, 1994 & Halliday, 1996, Biber et al., 1998) that was employed in a recent cross disciplinary doctoral research. The study was an Investigation into the linguistic resources that construct specialized knowledge in chemistry. The theoretical framework of systemic functional linguistics (SFL) outlined by Halliday and Matthiessen (2004 based in turn on Halliday (1994/1985)) was used as the main research tool. The system of taxis and logico semantic relations was demonstrated in relation 10 three analytical chemistry textbooks used at the undergraduate level 111 University of Malaya on the subject of chromatography (Rubinson & Rubinson, 1998, Skoog, et aI., 2000 and Christian, 2004). The principal markers of taxis and logico-semantic relations were identified according to 57 coding categories remodeled after Halliday & Matthiessen's (2004) conceptualization of taxis and logico semantic resources in English.  The research methodology used in the study was not a set of procedures nor did it follow any hierarchy or priority in the procedures for obtaining linguistic description. Hence, this paper will attempt to show how theory was used maximally to account for linguistic description and provide the foundations for explorations. The mediation of the range of semantic phenomena is through the researcher herself rather than through any inventory, questionnaire or machine, e.g. a parser or coder. Hence, this paper will discuss how theoretical issues  such as the coding decisions, interpretation of complex grammatical constructions and association patterns, overlapping categories and other Indeterminacies were resolved using a manual, clause by clause  analysis. The analysis of data involved the constant comparing of instances of one category with another in an attempt to refine the patterns that emerge. This paper will attempt to demonstrate the research design in a stepwise fashion which reflects the various dimensions to the analysis. Finally, the potential of a heuristic-grounded theory document analysis-qualitative approach for encoding experiential meaning is outlined.